The Effect of Liquidity Ratio, Profitability Ratio, Company Size, and Leverage on Bond Rating in Construction and Real Estate Company - Rindi Kumala Sari, Siti Nurlaela & Kartika Hendra Titisari (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to determine the significance influence of liquidity ratio,profitability ratio, company size and leverage to bond’s rating on construction andreal estate companies. The data in this research is secondary data obtained fromIndonesia Stock Exchange. The sample used in this study was 16 companies thatissue obligation and listed on Indonesia Stock Exchange in 2014-2016, withpurposive sampling method. Methods of data analysis used in this study wasmultiple linear regression test. The data processed by using SPSS 17. Based on theresult of the research that has been done, then it can be taken a few conclusions,namely: Liquidity ratio does not affect the bond’s rating. Profitability ratio affectthe bond’s rating. Company size does not affect the bond’s rating. And Leveragealso does not affect the bond’s rating.Keywords : Bond’s rating, Liquidity, Profitability, Size, Leverage.